Arnobe le Jeune et la Passion de Sébastien (Bhl 7543) - Lanéry, Cécile (Revue d'études augustiniennes et patristiques, 2007)
Among the late antique « epic Passions », the Sebastian Passion (BHL 7543) is of major importance for its highly literate style and its striking medieval posterity. It was written in Rome near 430 by an anonymous author. This latter was probably Arnobius Junior, whose exegetic and doctrinal work (Praedestinatus, Conflictus cum Serapione, Commentarii in Psalmos, Ad Gregoriam) tallies exactly with the same period (430-450). The Sebastian Passion can be attributed to Arnobius on the basis of thematic, linguistic and stylistic convergences as well as textual parallels.